1989
DOI: 10.1128/mcb.9.5.2034
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae CKS1 gene, a homolog of the Schizosaccharomyces pombe suc1+ gene, encodes a subunit of the Cdc28 protein kinase complex.

Abstract: The Saccharomyces cerevisiae gene CDC28 encodes a protein kinase required for cell cycle initiation. In an attempt to identify genes encoding proteins that interact with the Cdc28 protein kinase, high-copy plasmid suppressors of a temperature-sensitive cdc28 mutation were isolated. One such suppressor, CKS1, was found to encode an 18-kilodalton protein that shared a high degree of homology with the suc1+ protein (p13) of Schizosaccharomyces pombe (67% amino acid sequence identity). Disruption of the chromosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
179
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 197 publications
(184 citation statements)
references
References 37 publications
4
179
1
Order By: Relevance
“…Cloning CKS 1 homologs from human cells CKS1 from S. cerevisiae and sucl + from S. pombe are 67% identical at the amino acid level (Hadwiger et al 1989a). By comparison of the amino acid sequences of these proteins, two degenerate oligonucleotides were designed that could be used in the polymerase chain reaction (PCR)(C. Saiki et al 1988)to amplify a region of 198 bp from the S. cerevisiae CKS1 gene and from an intronless version of the S. pombe sucl + gene (obtained from J.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cloning CKS 1 homologs from human cells CKS1 from S. cerevisiae and sucl + from S. pombe are 67% identical at the amino acid level (Hadwiger et al 1989a). By comparison of the amino acid sequences of these proteins, two degenerate oligonucleotides were designed that could be used in the polymerase chain reaction (PCR)(C. Saiki et al 1988)to amplify a region of 198 bp from the S. cerevisiae CKS1 gene and from an intronless version of the S. pombe sucl + gene (obtained from J.…”
Section: Resultsmentioning
confidence: 99%
“…7B, lane 1; Hadwiger et al 1989a). When the Ckshs-Sepharose beads were incubated with extracts from a strain carrying a temperature-sensitive allele of CDC28, cdc28-4 (from which no Cdc28 activity is detected in the in vitro assay; Reed et al 1985;Mendenhall et al 1987), no significant activity was observed against histone H1 and no p40 phosphorylation was detectable.…”
Section: Ckshsl and Ckshs2 Bind To The Cdc2/cdc28 Protein Kinase Frommentioning
confidence: 99%
See 3 more Smart Citations